Regional logistics, carbon emission index and green financial performance enhancement configuration: a comparative study based on 30 Chinese provinces - Muyun Li; Muyun Li; Muyun Li; Lihua Wang; Zhongyan Liu; Zhongyan Liu; Qile He (Frontiers in Energy Research, 2023)
In recent years, because of the increasingly severe global environmental protection situation and the superimposed effect of the new crown epidemic, the importance of green finance has been highlighted and gradually elevated to an important future development strategy for the country. However, it is unclear how to improve the effectiveness of green finance in each province. Using 30 Chinese provinces and regions as research samples, this paper summarizes five influencing factors, including regional logistics, carbon emission index, regional finance, economic level, and environmental regulation. Considering the complex causal relationship between factors and green finance performance, fsQCA is used to explore the different configurations formed in the process of developing green finance in each province. The results comprise four different configurations for high performance and four types of configurations for the absence of high performance. Currently, with the regional green finance development model still in its infancy, regional logistics and carbon emission index factors play a key role in stimulating the development of green finance in the provinces and regions. This study has important theoretical and practical significance for the construction of regional green financial system and local government performance appraisal system with local characteristics in each province of China, and provides locally adapted policy suggestions for different provinces to achieve optimal allocation of resources.